2002
DOI: 10.1002/pros.10137
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavonoid equol modulates the growth of benign and malignant prostatic epithelial cells in vitro

Abstract: Equol is a biologically active metabolite of daidzein that has potent antiproliferative effects on benign and malignant prostatic epithelial cells at concentrations that can be obtained naturally through dietary soy consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 62 publications
9
94
0
1
Order By: Relevance
“…Polyphenols inhibited the growth of normal prostatic epithelial cells (Hedlund et al 2003), with inhibition of the IGF-I signal transduction pathway implicated in this activity , Wang S et al 2003. These findings provide further support for potential chemopreventive activity of polyphenols because IGF-I activity has been linked to increased prostate cancer risk (Pollak et al 2004).…”
Section: Chemopreventionmentioning
confidence: 73%
See 2 more Smart Citations
“…Polyphenols inhibited the growth of normal prostatic epithelial cells (Hedlund et al 2003), with inhibition of the IGF-I signal transduction pathway implicated in this activity , Wang S et al 2003. These findings provide further support for potential chemopreventive activity of polyphenols because IGF-I activity has been linked to increased prostate cancer risk (Pollak et al 2004).…”
Section: Chemopreventionmentioning
confidence: 73%
“…These findings provide further support for potential chemopreventive activity of polyphenols because IGF-I activity has been linked to increased prostate cancer risk (Pollak et al 2004). In many cases, the growth inhibitory concentrations of these compounds were within the range that can be attained through dietary consumption (Hedlund et al 2003). In contrast, prostate cancer cell lines show variable responses to polyphenols, and in many cases require supraphysiological concentrations for maximal effect (Hedlund et al 2003).…”
Section: Chemopreventionmentioning
confidence: 78%
See 1 more Smart Citation
“…Equol has been implicated with daidzein activities in vivo after ingestion of soy foods and has been shown to be more potent than daidzein in vitro (8,55,56). Equol is a chiral molecule capable of existing in two enantiomeric forms: R-(ϩ) equol and S-(Ϫ) equol; the latter is the natural diasteromer produced by intestinal bacteria (6,11).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Additionally, equol can bind sex hormone-binding globulin 15,16 and 5a-dihydrotestosterone 14 and inhibit the growth of prostate cells in vitro and in vivo. 14,17 Therefore, equol can act as an anti-androgen and inhibit the development of sex hormone-dependent tumors such as breast cancer and prostate cancer. 14 In our previous study, we demonstrated that the proportion of equol producers was significantly smaller in the patient group with prostate cancer than in the cancer-free control group and that this proportion was significantly smaller in patients with poorly differentiated adenocarcinoma than in those with well or moderately differentiated adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%